Ophelia - Gingras, Charlotte 1943- (Groundwood Books / House of Anansi Press, 2018)
Ophelia hides under oversized clothing, and hardly speaks-- until the day a visiting author gives a talk in the school library. She speaks about what it means to create art, and at the end thanks Ophelia for asking the first question, giving her a blue notebook with her address on it. The idea that someone might care is enough for Ophelia to keep writing, an escape from her real life. At night she creates graffiti around town, leaving little broken hearts as her tag. She finds an abandoned building to use as a workshop, and finds that a classmate, Ulysses, is also using the space to repair an old van. The two forge a fraught but growing friendship until intruders invade their sanctuary
Keywords: Teenage girls / Fiction; Diaries / Fiction; Graffiti artists / Fiction; Marginality, Social / Fiction; Graffiti / Fiction; Diaries; Graffiti artists; Marginality, Social; Teenage girls; Self-acceptance / Young adult fiction; Friendship / Young adult fiction; Diaries / Young adult fiction; Family problems / Young adult fiction; Graffiti artists / Young adult fiction; Misfits / Young adult fiction; Coming of age / Young adult fiction; Bildungsromans; Epistolary fiction; Fiction; Jugendbuch